2012
DOI: 10.1016/j.brainres.2012.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Targeting inhibitory neurotransmission in tinnitus

Abstract: Tinnitus perception depends on the presence of its neural correlates within the auditory neuraxis and associated structures. Targeting specific circuits and receptors within the central nervous system in an effort to relieve the perception of tinnitus and its impact on one’s emotional and mental state has become a focus of tinnitus research. One approach is to upregulate endogenous inhibitory neurotransmitter levels (e.g. glycine and GABA) and selectively target inhibitory receptors in key circuits to normaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 106 publications
(152 reference statements)
3
57
0
Order By: Relevance
“…The thalamus, which regulates the flow of sensory information to and from the auditory cortex, is thought to play an important role in the perception of tinnitus [9,14]. Consistent with this view, we observed that the thalamus showed decreased functional connectivity with the primary and associative auditory cortex, specifically the STG (Brodmann's area 42) and MTG (Brodmann's area 21).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The thalamus, which regulates the flow of sensory information to and from the auditory cortex, is thought to play an important role in the perception of tinnitus [9,14]. Consistent with this view, we observed that the thalamus showed decreased functional connectivity with the primary and associative auditory cortex, specifically the STG (Brodmann's area 42) and MTG (Brodmann's area 21).…”
Section: Discussionsupporting
confidence: 84%
“…However, the mechanisms responsible for these functional changes are unknown, but could involve aberrant inhibition [9]. Hypothetically, impaired thalamic gating could directly affect the function of the auditory cortex or alternatively alter the function of subcortical regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several pLGIC receptors, notably the nicotinic acetylcholine receptor and the GABA A receptor (GABA A R), have long been important therapeutic targets, and the GlyR has recently emerged as a potential target for indications including inflammatory pain sensitization (10 -12), opioid-induced breathing depression (13), tinnitus (14), and temporal lobe epilepsy (15). It is important to resolve the mechanisms by which the structure of pLGIC receptors changes between the closed and open states to design new drugs that bias the receptor toward the desired conformation.…”
mentioning
confidence: 99%
“…Firstly, other conventional tinnitus inducers such as salicylate or quinine had a postulated convergent mechanism that either directly or indirectly targeted the GABAergic inhibitory interneuron of the afferent pathway in the auditory cortex, resulting in disrupted plasticity of excitation-inhibition and resulting hyperactivity (Noreña et al, 2010). In addition, it should be noted that age-related tinnitus co-exhibited decreased inhibitory neurotransmission in the auditory cortex and along the auditory subcortical pathway (Caspary et al, 2013;Richardson et al, 2012). We used a simplified cortical disinhibition model with the GABA A antagonist pentylenetetrazol.…”
Section: Clinical Relevance Of Kmentioning
confidence: 99%